A new handhold device for measuring resting metabolic rate and oxygen consumption - Nieman, David C; Trone, Gregory A; Austin, Melanie D (Journal of the American Dietetic Association, 2003)
Objective The purpose of this study was to test a new handheld device, the BodyGem (HealtheTech Inc., Golden, CO), that measures resting metabolic rate (RMR). Subjects/design Sixty-three adults (43 women, 20 men) (mean±SD, age 41.3±11.2 years and body mass index, 26.5±6.6 kg/[m.sup.2]) were tested during two separate sessions within a 2-week period, and, in each session, two BodyGem and two Douglas bag RMR measurements were made in a random and counterbalanced order. Main outcome measures Resting oxygen consumption and energy expenditure. Statistical analyses performed A 2 (methods) X 4 (time points) repeated measures ANOVA, Pearson product-moment coefficients, Bland-Altman plots. Results Within session reliability for measurement of [O.sub.2], consumption was high on both days for the BodyGem (r=0.97). During the 4 single tests, BodyGem and Douglas bag [O.sub.2] consumption values were significantly correlated (r=0.81-0.87), with SEEs ranging from 22 to 28 mL * [min.sup.-1]. Mean [O.sub.2] consumption and RMR values for all 4 tests were 241±46 and 240±45 mL * [min.sup.-1] (r=0.91, SEE 18.7 mL * [min.sup.-1]) and 1,657±324 and 1,650±307 kcals * [day.sup.-1] (r=0.91, SEE 134 kcals * [day.sup.-1]) for the BodyGem and Douglas bag methods, respectively. Applications/conclusions These data indicate that the BodyGem is an accurate and reliable device for measuring oxygen consumption and calculating RMR during repeated tests within a day, single tests on separate days, or when measurements are averaged. J Am Diet Assoc. 2003;103:588-593.